2014
DOI: 10.2341/11-479-l
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Shrinkage of Different Types of Composite Resins and Microleakage With and Without Liner in Class II Cavities

Abstract: The use of RMGIC liner with composite resin restorations reduces microleakage. The silorane-based composite showed lower volumetric polymerization shrinkage than methacrylate-based composites. SUMMARYAim: To determine the volumetric polymerization shrinkage of four different types of composite resin and to evaluate microleakage of these materials in class II (MOD) cavities with and without a resin-modified glass ionomer cement (RMGIC) liner, in vitro.Materials and Methods: One hundred twentyeight extracted hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
0
35
0
3
Order By: Relevance
“…However, two studies showed that, after being subjected to thermal and mechanical stress, luting directly to dentin (conventional technique) resulted in superior marginal adaptation as compared with CMR composite on dentin (21,23). The present findings might have been affected by polymerization shrinkage of the resin composite materials used for making the CMR and luting the overlay (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 58%
“…However, two studies showed that, after being subjected to thermal and mechanical stress, luting directly to dentin (conventional technique) resulted in superior marginal adaptation as compared with CMR composite on dentin (21,23). The present findings might have been affected by polymerization shrinkage of the resin composite materials used for making the CMR and luting the overlay (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 58%
“…This process, in turn, permits bacterial ingress with recurrent caries, sensitivity, possible pulpal inflammation, and, finally, restoration removal and reinsertion as final outcomes. 9,11,17 Solutions for some of these specific material and clinical dilemmas have included the introduction of ''packable'' and ''flowable'' composites-allowing for enhanced adaptability of overlying materials; the usage of different insertion techniques (incremental vs bulk); and different restoration delivery methods (thermal and/or sonic energy). [15][16][17][18][19][20][21][22][23] However, many of these restorative solutions have shown conflicting results with regard to the effects on material shrinkage and marginal microleakage of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,17 Solutions for some of these specific material and clinical dilemmas have included the introduction of ''packable'' and ''flowable'' composites-allowing for enhanced adaptability of overlying materials; the usage of different insertion techniques (incremental vs bulk); and different restoration delivery methods (thermal and/or sonic energy). [15][16][17][18][19][20][21][22][23] However, many of these restorative solutions have shown conflicting results with regard to the effects on material shrinkage and marginal microleakage of contaminants. [15][16][17][18][19][20][21][22][23] Recently, a composite delivery system together with a proprietary composite formulation has been introduced to the market to compensate for the misgivings (physical, material, and clinical) of composite resin science technology.…”
Section: Introductionmentioning
confidence: 99%
“…В исследованиях in vitro E. Karaman (2014) [9] и P. Bogra (2012) [10] не выявлено преимуществ нанокомпо-зитов (Ceram X и Filtek Supreme XT) в усадке при полиме-ризации и краевой проницаемости пломб перед традици-онными композитами и композитом на основе силорана (Filtek Silorane).…”
Section: стоматология 2 2016unclassified